Antiferromagnetic Spintronics: Electric‐Field‐Controlled Antiferromagnetic Spintronic Devices (Adv. Mater. 12/2020). Issue 12 (24th March 2020) - Yan, Han; Feng, Zexin; Qin, Peixin; Zhou, Xiaorong; Guo, Huixin; Wang, Xiaoning; Chen, Hongyu; Zhang, Xin; Wu, Haojiang; Jiang, Chengbao; Liu, Zhiqi
Abstract : Antiferromagnetic spintronic devices are capable of magnetic‐field‐insensitive, ultrafast (picosecond‐timescale) information storage and processing, as well as building artificial neurons for neuromorphic computing. In article number 1905603, Zhiqi Liu and co‐workers comprehensively review different electric‐field approaches for harnessing spins in antiferromagnets, which are of ultralow power owing to Joule heating suppression.